Survivors of Stroke Face Greater Social Risks Than Adults Who Have Not Had a Stroke: Results From a Nationwide Study - Lesli E. Skolarus; Ran Bi; Chun Chieh Lin; Sara Hassani; Yvonne Curran; James F. Burke (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Integrating social and medical care is one strategy to promote health equity. Yet, little is known about the prevalence of health‐related social risks (social risks) among survivors of stroke. We sought to determine the prevalence of social risks among survivors and to quantify how social risks change after a stroke. Methods and Results We conducted a cross‐sectional analysis of community‐dwelling older adults (age≥65) from the National Health and Aging Trends Survey. Six core social risks were examined: medical financial risks, utility financial risks, housing, nutrition, social isolation, and transportation. We used a Poisson regression model to explore the association of social risks and history of stroke, accounting for sociodemographic factors (age, sex, race or ethnicity, education, income, rurality) and comorbidities. In a separate series analysis, we determined the association between stroke and changes in social risks in a propensity‐matched cohort. Of 5834 older adults, 673 were survivors of stroke. In cross‐sectional analysis, survivors of stroke were more likely to report social risks than older adults without a history of stroke (54.3% versus 40.2%, P<0.01). The largest difference between survivors of stroke and older adults who have not had a stroke was transportation disadvantage (9.7 versus 4.0, P<0.01). After adjustment, a history of stroke was not associated with social risks (incidence rate ratio, 1.1 [95% CI, 0.9–1.2], P=0.37). In the series analysis, there was no change in the average number of social risks after the stroke among those who had a stroke (incidence rate ratio, 1 [95% CI, 0.9–1.2], P=0.78). After a stroke, social risks were stable in 66.3%, increased in 19.4%, and decreased in 14.3% of stroke survivors. Conclusions Over half of older adults who have had a stroke report experiencing a social risk, with a 35% higher prevalence compared with older adults who have not had a stroke. Thus, social risks disproportionately affect survivors of stroke.